2022
DOI: 10.1186/s41256-022-00253-3
|View full text |Cite
|
Sign up to set email alerts
|

Regional years of life lost, years lived with disability, and disability-adjusted life-years for severe mental disorders in Guangdong Province, China: a real-world longitudinal study

Abstract: Background To understand the magnitude and spatial–temporal distribution of the regional burden attributable to severe mental disorders is of great essential and high policy relevance. The study aimed to address the burden of severe mental disorders by evaluating the years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) in Guangdong, China. Methods We undertook a longitudinal study based on a multicenter databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This was a nationwide study that comprehensively evaluated the trend of allocation of human resources in China's rehabilitation institutions by longitudinal and horizontal comparison. Rehabilitation is a fundamental health service for people with a variety of health conditions, and it primarily focuses on improving their ability to function well in society and on reducing the impact of disability ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…This was a nationwide study that comprehensively evaluated the trend of allocation of human resources in China's rehabilitation institutions by longitudinal and horizontal comparison. Rehabilitation is a fundamental health service for people with a variety of health conditions, and it primarily focuses on improving their ability to function well in society and on reducing the impact of disability ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Years Lived with Disability : Long-term disability due to a given cause including blindness, moderate vision impairment and severe vision impairment ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Schizophrenia is a common and debilitating disorder that affects approximately 1% of the global population, with an age-standardized prevalence of 287.4 per 100,000 people [ 3 , 4 ]. Previous studies have suggested that the lifetime prevalence of mental disorders in China may be estimated at 15.8-16.6%, and the lifetime prevalence and 12-month prevalence of schizophrenia were both 0.6% [ 5 , 6 ]. However, these results may be underestimated, partly because of the stigma attached to the illness, and partly owing to the underdiagnosis and undertreatment of the illness in community hospitals, which results in the chronicity of the illness.…”
Section: Introductionmentioning
confidence: 99%